Building your online store with WordPress and WooCommerce : learn to leverage the critical role e-commerce plays in today's competitive marketplace - Sims, Lisa (Apress, 2018)
Teaches you all about e-commerce and how to create your own online shop using WordPress and WooCommerce. Regardless of a business's size, e-commerce helps level the playing field, increases a business's exposure, allows companies to reach customers globally, and streamlines the fulfillment process. In the past, e-commerce websites were expensive, technically difficult, and time-consuming to create but not anymore. WordPress and WooCommerce together are a complete e-commerce solution that can be used to sell both physical and digital products online. You'll learn how to install WordPress and how to plan your e-commerce solution with WooCommerce as well as install, create, secure, test, and market a sample online store. Save time and money by planning your own e-commerce strategy without paying expensive consultants. Increase your brand and products' or services' exposure to your target customers, and increase sales by offering target customers the ability to purchase products online as well as reach potential customers globally.